Development and validation of a food and nutrition literacy questionnaire for Chinese parents of children with functional constipation (FNLQ-p) - Yang, Jie; Wang, Hui; Shen, Yanchi; Yang, Hui; Huang, Yan; Cao, Jinjin (Frontiers in Nutrition, 2025)
ObjectivesChildhood functional constipation is a widespread condition with a global prevalence. Dietary interventions play a crucial role in the management of childhood constipation. Hence, the development and validation of a specialized food and nutrition literacy assessment tool for parents of school-aged children with functional constipation is of paramount significance.MethodsOn the basis of literature review, the first draft was formed, and the results of expert correspondence and pre survey were combined to delete and modify the first draft. In the second stage, 459 parents of school-age children with constipation were invited to fill out the questionnaire. Item analysis, exploratory factor analysis, and confirmatory factor analysis were then conducted to assess the questionnaire's reliability and validity.ResultsThe final scale comprises 4 dimensions and 25 items. Exploratory factor analysis extracted four common factors (nutrition knowledge, nutrition skills, nutrition interaction, nutrition evaluation), and the cumulative variance contribution rate was 64. 532%. The content validity index (I-CVI) of each item level is 0.86–1, the content validity index (S-CVI) at the scale level is 0.96. The overall Cronbach'sα coefficient was 0.85. Confirmatory factor analysis supported the four-factor structure derived from exploratory analysis, with all relevant fit indices meeting standard criteria.ConclusionsThe food and nutrition literacy questionnaire developed in our study had good validity and reliability, making it a useful tool for assessing the food and nutrition literacy among parents of school-aged children diagnosed with functional constipation.